Maximum velocities in flexion and extension actions for sport - Jessop, D. M.; Pain, M. T. G. (Journal of Human Kinetics, 2016)
Speed of movement is fundamental to the outcome of many human actions. A variety of techniques can be implemented in order to maximise movement speed depending on the goal of the movement, constraints, and the time available. Knowing maximum movement velocities is therefore useful for developing movement strategies but also as input into muscle models. The aim of this study was to determine maximum flexion and extension velocities about the major joints in upper and lower limbs. Seven university to international level male competitors performed flexion/extension at each of the major joints in the upper and lower limbs under three conditions: isolated; isolated with a countermovement; involvement of proximal segments. 500 Hz planar high speed video was used to calculate velocities. The highest angular velocities in the upper and lower limb were 50.0 rad·s-1 and 28.4 rad·s-1, at the wrist and knee, respectively. As was true for most joints, these were achieved with the involvement of proximal segments, however, ANOVA analysis showed few significant differences (p<0.05) between conditions. Different segment masses, structures and locations produced differing results, in the upper and lower limbs, highlighting the requirement of segment specific strategies for maximal movements.